DEKONSTRUKSI KESAKRALAN DUNIA PEWAYANGAN : Sebagai Peninggalan Adiluhung melalui Manyura - Nurhadi, Taufik (LPPM Universitas PGRI Adi Buana Surabaya, 2014)
Abstrak The purpose of this study is to obtain the results of descriptions and explanations on puppet world deconstruction which is sacred and sublime masterpiece through the creative work of fiction, Manyura written by Yanusa Nugroho. The results of this literature review based on the approach prove that deconstruction in Manyura produce: (1) the lawsuit against submission of puppet history, (2) the degradation of intensity characterizations, and (3) demoralization figure Yudhishthira. The three forms of deconstruction express the social criticism to the behavior of Indonesian politics, especially in the Era of ORBA. Keywords: deconstruction, puppet, submission, degradation, demoralization.